Krzyż i chwała : błogosławiona Bronisława i Konwent Panien Norbertanek na Zwierzyńcu w Krakowie = The cross and glory : blessed Bronislava and Norbertine Canonesses Convent in Zwierzyniec, Cracow - Stefaniak, Piotr (Księgarnia św. Jacka, 2019)
Keywords: zwierzyniec; 👤 bronislava of kamień

Problem genezy formalnej prezbiterium w krakowskim kościele Norbertanek na Zwierzyńcu - Cierpisz, Szymon (Rocznik krakowski Towarzystwo Miłośników Historii i Zabytków Krakowa, 2018)
Keywords: zwierzyniec

Inwentarz dóbr konwentu zwierzynieckiego w roku Pańskim 1722 spisany - Kazusek, Szymon (Nasza Przeszłość, 2013)
The subject of this publication is the only remaining early-modern inventory of the estates of the convent of Premonstratensians at Zwierzyniec near Cracow. This manuscript contains the description of the real estates in twenty villages being in the property of the Zwierzyniec convention in 1722. The inventory is an excellent source for the research on the farm economy in convent estate. The names of convent villages which the described real estates come from have in huge majority endured until contemporary times. At present some places are within the administrative borders of Cracow, Krzeszowice or Będzin, other exist under previous or modified names, whereas one of the described villages (Zakościele) has not remained until present times. Analysing the content of the inventory it is possible to obtain detailed information about the size, the state and the organisation of the buildings that were convent property, as well as about the leases and their financial aspects. The image emerging after studying the inventory shows a wide diversity of technical condition of farm buildings. What is more, the presented description includes information about buildings in very bad state as well as about renovated or new ones.
Keywords: zwierzyniec